Evaluation of Probability Discounting : a Comparison of Real and Hypothetical Rewards and a Molecular Analysis of the Effect of Recent History on Discounting - Steinhauser, Haley (My University, 2012)
Past research has analyzed whether or not there is a reward effect on the degree to which individuals discount delayed and probabilistic rewards (Hinvest & Anderson, 2010; Johnson & Bickel, 2002; Madden, Begotka, Raiff, & Kastern, 2003). Previous research evaluating whether or not there is a reward effect on discounting (e.g., delay and probability) has resulted in inconsistent conclusions. The current within-subjects study reevaluated whether there is a reward-type effect in the probability discounting of real and hypothetical rewards, using a practical computer task with roulette-type wheels.
Color poster with text and graphs.
Keywords: Choice (Psychology); Reward (Psychology); Posters